2017
DOI: 10.1038/s41598-017-04291-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of SET/I2PP2A in canine mammary tumors

Abstract: Canine mammary tumor is the most common neoplasm in female dogs, and it has generated considerable attention as a translational model for human breast cancer. Ser/Thr protein phosphatase 2A (PP2A) plays a critical role as a tumor suppressor, and SET/I2PP2A, the endogenous inhibitory protein of PP2A, binds directly to PP2A and suppresses its phosphatase activity. Here, we investigated the role of SET in the tumorigenic growth in canine mammary tumor as well as in the sensitivity of tumors to existing therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
(51 reference statements)
0
16
1
Order By: Relevance
“…We and others have reported previously that SET KD suppressed Akt signaling (13,24), ERK1/2 signaling (24), mTOR signaling (25), NFkB signaling, and b-catenin signaling (26). However, we observed that SET KD did not have a marked effect on these cell-signaling molecules in MKN45 cells ( Fig.…”
Section: Set/i2pp2a Associates With Pp2a-b56 Complex and Stabilizes Econtrasting
confidence: 45%
“…We and others have reported previously that SET KD suppressed Akt signaling (13,24), ERK1/2 signaling (24), mTOR signaling (25), NFkB signaling, and b-catenin signaling (26). However, we observed that SET KD did not have a marked effect on these cell-signaling molecules in MKN45 cells ( Fig.…”
Section: Set/i2pp2a Associates With Pp2a-b56 Complex and Stabilizes Econtrasting
confidence: 45%
“…The nature of HRV dynamics is the object of lively debates (Glass, 2009 ; Sassi et al, 2009 ; Valenza et al, 2017 ). The question of whether or not the normal heart rate is chaotic (Glass, 2009 ) is leading investigators to refine the concept of complexity variability using the tools of non-linear dynamics (Valenza et al, 2017 ) and to restate the multifractal nature of heart rate variability (Sassi et al, 2009 ). We focus on the important role of crucial events , advocated in 2002 by Allegrini et al ( 2002 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Inhibition of SET methyltransferase by shRNA and FTY720, reported to directly interact with SET proteins, suppressed cell proliferation, colony formation, and in vivo tumor growth of canine mammary and osteosarcoma cell lines. Furthermore, SET knockdown repressed mTOR and NF-kB signaling in both types of canine cancer (223,224). Using BB-Cl-Amidine (BB-CLA) to inhibit protein-arginine deiminases (PADs) resulted in the decrease of viability and tumorigenicity of FIGURE 3 | Effects of some alternative epigenetic inhibitors in canine mammary cancer cells.…”
Section: Alternative Epigenetic Targetsmentioning
confidence: 99%